(untitled) (Heritage, 2022)
The paper pays attention to the mutesellim of Novi Pazar Yusuf Bey (1838–1839, 1841–1842, 1842–1851), the Serbian people and the reflection of the Tanzimat reforms in the territory under his control – Novi Pazar, Mitrovica, Sjenica, Nova Varoš, Trgovište and Bihor kaza. It is pointed out that Yusuf Bey in the period 1838–1842. fought for the position of Novi Pazar mutesellim and that his administration ended in 1851, after the successful military action of the Rumelia serasker Omer Pasha Latas in the Bosnian Eyalet. In the mentioned year, the Sanjak of Novi Pazar was officially formed, which, in addition to the kazas that were under the control of Yusuf Bey, also included the Višegrad kaza. During the rule of Yusuf Bey, Serbs were exposed to constant violence, except in the period from 1844 to 1848, when a relatively peaceful situation prevailed. Serbs most complained about the representatives of the executive power who committed all kinds of violence (rapes, attempted violent islamization, murders).